2019
DOI: 10.3400/avd.ra.18-00076
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pharmacological Approaches for Treating Abdominal Aortic Aneurysm

Abstract: Abdominal aortic aneurysm (AAA) is considered to be a potent life-threatening disorder in elderly individuals. Although many patients with a small AAA are detected during routine abdominal screening, there is no effective therapeutic option to prevent the progression or regression of AAA in the clinical setting. Recent advances in molecular biology have led to the identification of several important molecules, including microRNA and transcription factor, in the process of AAA formation. Regulation of these fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 100 publications
(126 reference statements)
0
12
0
Order By: Relevance
“…Future perspectives of pharmacological approaches to limit AAA growth also include nucleic acid drugs that target mRNAs, microRNAs, or transcription factors in a sequence-specific manner to interfere with key molecules in AAA pathogenesis [ 249 ].…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…Future perspectives of pharmacological approaches to limit AAA growth also include nucleic acid drugs that target mRNAs, microRNAs, or transcription factors in a sequence-specific manner to interfere with key molecules in AAA pathogenesis [ 249 ].…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…Their efficacy on AAA formation had been confirmed in experimental studies. However, there is no evidence for beneficial in clinical trials 5 . Therefore, the treatment of small AAA remains an imperative clinical problem 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, our data suggest that lymphocyte activation and proliferation mechanisms could be crucial for amplifying the local antigen-driven immune response in the PVAT of AAA patients. Interfering with NK-kB signaling [ 45 ] in immune cells may, thus, have a significant impact on the evolution of AAA. Although immune-suppressive treatment should be carefully evaluated [ 46 ], selectively inhibiting NF-kB signaling in activated and proliferating lymphocytes in dysfunctional AAA PVAT may be a targeted therapeutic intervention without compromising the healthy effect mediated by NF-kB in other immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, an immune phenotyping analysis in human AAA samples recently found that T-lymphocytes are the primary cell leukocyte population in AAA, with the largest concentration in PVAT, and that these PVAT-associated T-lymphocytes correlated with the severity of the disease [ 66 ]. Assessing the presence of a locally restricted, antigen-driven clonal expansion in PVAT of AAA could, thus, be the goal of future studies, which will allow for the precise detection of pathogenic lymphocytes for direct interference treatment [ 45 ], possibly through the above-suggested disease gene targets.…”
Section: Discussionmentioning
confidence: 99%